Determine The Implications Of Presidential Regulation (Perpres) Number 82 Of 2021 Funding For Islamic Boarding Schools - Hannum, Ikhsanti; Sirozi, M.; Sumanti, Soliha Titin (Universitas Dharmawangsa Medan, 2024)
This research aims tothe Government's concern for Islamic boarding schools.This concern was identified by Presidential Regulation (PERPRES) Number 82 of 2021, which concerns the funding of Islamic boarding schools, Islamic boarding school endowment funds, and the prospects for Islamic boarding schools following the stipulation ofPERPRES No. 28 of 2021, as well as political aspects in the stipulation of the PERPRES. Consideringthat Islamic boarding schools are the oldest educational institutions in Indonesia, with their distinctive educational approach, they have also played a pivotal role in the Indonesian independence movement. They are an integral part of the Indonesian educational landscape, contributing to the production of high-quality educational outcomes. This paper draws upon a range of key literature on the subject, which has been selected, organized and categorized according to their suitability for the purposes of this study. The contents of the literature were subjected to a rigorous analysis in order to ensure their suitability as material for the completion of this paper. This explanation is characteristic of library research, which employs content analysis techniques. The findings of the research indicate that the primary functions of Islamic boarding schools are education, da'wah and community empowerment.The existence of political power to pass the Islamic Boarding School Law and the Islamic Boarding School Endowment Fund contained in PERPRES no. 28 of 2021 is a legal umbrella for Islamic boarding school institutions to receive funds from the APBN, APBD in the form of grants, as well as non-binding assistance from other parties.The implications of this government policy have a significant impact on Islamic boarding schools, which are tasked with improving the quality of education in these institutions. However, Islamic boarding schools must also navigate the challenges of maintaining their unique curriculum in the context of government regulations. The primary implications of the establishment of the PERPRES in question are the requirement to register Islamic boarding schools (legalizing Islamic boarding schools administratively) and changes to the curriculum used (the incorporation of non-religious knowledge).